2020
DOI: 10.3390/ijerph17041127
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Associations Between Land Use and Infectious Disease: Zika Virus in Colombia

Abstract: Land use boundaries represent human-physical interfaces where risk of vector-borne disease transmission is elevated. Land development practices, coupled with rural and urban land fragmentation, increases the likelihood that immunologically naïve humans will encounter infectious vectors at land use interfaces. This research consolidated land use classes from the GLC-SHARE dataset; calculated landscape metrics in linear (edge) density, proportion abundance, and patch density; and derived the incidence rate ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The last WHO epidemiological update on ZIKV, dating of July 2019, reported that there were still 87 countries and territories with autochthonous ZIKV transmission, distributed across four of the six WHO regions (African, Americas, South-East Asia, and Western Pacific Regions) [8]. The re-emergence of ZIKV across the Americas was linked to changes in land use due to urbanization, changing of agricultural practices and deforestation [9]. Currently, ZIKV is endemic in all tropical areas of the world, similarly to DENV; and nearly half of the global population lives in areas at risk of ZIKV infection [10].…”
Section: Epidemiologymentioning
confidence: 99%
“…The last WHO epidemiological update on ZIKV, dating of July 2019, reported that there were still 87 countries and territories with autochthonous ZIKV transmission, distributed across four of the six WHO regions (African, Americas, South-East Asia, and Western Pacific Regions) [8]. The re-emergence of ZIKV across the Americas was linked to changes in land use due to urbanization, changing of agricultural practices and deforestation [9]. Currently, ZIKV is endemic in all tropical areas of the world, similarly to DENV; and nearly half of the global population lives in areas at risk of ZIKV infection [10].…”
Section: Epidemiologymentioning
confidence: 99%
“…The mechanical parameters that will be affected are difficult to estimate precisely, so empirical models are more feasible [ 6 ]. For example, a series of disparate phenomena will favor vector-borne diseases, from land-use change [ 8 , 9 ], human migration [ 10 ] and urbanization [ 3 ], to the rate of insect development [ 11 , 12 ], to name just a few. As such, the multifactorial nature of vector-borne diseases requires data on each of the factors that favor the increase in transmission of those diseases, in order to assemble different parts of the puzzle and understand the main causes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies have used LCLU maps at multiple spatial resolutions to predict the disease transmission risk or to study the role of LCLU in disease transmission based on the links between vector habitat preferences, LCLU classes, and disease incidence [ 6 , 10 ]. In contract, others have associated LCLU based landscape metrics such as edge density, patch density, and proportion of land use with disease risk [ 9 ].…”
Section: Discussionmentioning
confidence: 99%